Hyperbaric Oxygen Therapy : A new Evolving Future Perspective for Management of Mucormycosis and COVID 19 in Children in Developing Countries - Lakra, Mahaveer; Taksande, Amar; Lakhkar, Bhavana; Damke, Sachin; Lakra, Ashwini (Journal of Nepal Paediatric Society, 2022)
The SARS COVID-19 virus has arisen as a major hazard to mankind, posing harm to the whole world population. During the second COVID wave, mucormycosis has emerged as one of the deadliest and most devastating illnesses. Mucormycosis is strongly associated with diabetes, prolonged use of steroids, prolonged hospitalisation and immunocompromised states. Children have also been affected by this badly. Hyperbaric oxygen therapy is a non-invasive, cost-effective and painless therapy where 100% oxygen is given to patients under high atmospheric pressure in small tents or chambers. It helps in tissue regeneration and angiogenesis. Hyperbaric oxygen has proved to be effective in the treatment of oculo-rhino-cerebral mucormycosis. Various studies have proved its role in the management of mucormycosis and acute respiratory distress syndrome associated with COVID-19 infection. The advantages of hyperbaric oxygen are same in children as in adults with minimum side effects. Hyperbaric oxygen therapy can be one of the good adjunctive therapies in the management of mucormycosis. It is found to be safe in the treatment of COVID-19 infection, but data is still limited on its use and further studies are needed. This article is all about its use, its efficacy, and future perspectives in the management of mucormycosis and COVID-19 in view of the arrival of the third COVID wave in developing countries like India.